PROTEIN RESIDUE ANALYSIS OF LITHIC ARTIFACTS FROM HhOv-113, HhOv-302, HhOv-304, HhOv-308, HhOv-323, HhOv-332, HhOv-340, HhOv-394, and HhOv-468, ALBERTA, CANADA - Milligan, Jennifer L.B.; Cummings, Linda Scott (PaleoResearch Institute) (the Digital Archaeological Record)
Sites HhOv-113, HhOv-302, HhOv-304, HhOv-308, HhOv-323, HhOv-340, HhOv-394, and HhOv-468, located near Fort McMurray in northeast Alberta yielded evidence of Early, Early Middle, and Middle Prehistoric Period (including the Beaver River Complex) occupations. A total of thirteen lithic artifacts were submitted from these sites for protein residue testing. One sample that produced a weak positive result to elephant antiserum during a previous analysis will be retested here. Analysis of protein residues extracted from the artifact surfaces can provide information concerning processing/hunting of animal resources with these tools.